Relation between peripheral blood inflammatory indices and severity of central retinal artery occlusion - Hu,Weiwen; Huang,Yikeng; Zhou,Qiong; Huang,Xionggao (PeerJ, 2024)
Background Central retinal artery occlusion (CRAO) has been identified as an acute emergency resulting in vision loss, with its pathogenesis potentially involving systemic inflammation and abnormal lipid metabolism. Over recent years, it has been established that peripheral blood inflammatory indices, including the neutrophil-to-lymphocyte ratio (NLR), the systemic immunoinflammatory index (SII), and the monocyte-to-high-density lipoprotein ratio (MHR), play significant roles in assessing systemic inflammation and lipid metabolism. However, the role of these indices in assessing the severity of CRAO has rarely been explored. This study aimd to investigate the relationship between these inflammatory indices and the severity of CRAO. Methods This was a retrospective clinical study with a total of 49 CRAO patients and 50 age- and sex-matched controls involved. The patients with CRAO were divided into three groups (13 with incomplete CRAO, 16 with subtotal CRAO and 20 with total CRAO). Data were compared across these groups, and additionally, correlation analysis, restricted cubic spline plots, and receiver operating characteristic curve analysis were performed. Results The values of NLR, SII and MHR were significantly higher in the CRAO group compared to controls (NLR: 2.49(1.71,3.44) vs 1.60(1.24,1.97), P<0.001; SII: 606.46(410.25,864.35) vs 403.91(332.90,524.31), P=0.001; MHR: 0.33(0.26,0.44) vs 0.25(0.21,0.34), P<0.001). MHR was also significantly higher in total CRAO than in incomplete CRAO and subtotal CRAO (0.41(0.32,0.60) vs 0.29(0.21,0.43), P=0.036; 0.41(0.32,0.60) vs 0.29(0.23,0.38), P=0.017). Significant positive associations were found between MHR, NLR, SII and both the incidence (all P<0.001) and severity (P<0.001, P<0.001, P=0.003, respectively) of CRAO. MHR had a linear relationship with both the occurrence and severity of CRAO (P-overall=0.013, P-non-linear=0.427 and P-overall=0.013, P-non-linear=0.825). Combining MHR and NLR significantly improved diagnostic efficacy for CRAO and total CRAO, with area under the curve of 0.816 and 0.827, respectively, compared to using MHR alone (0.705 and 0.816). Conclusion Elevated levels of peripheral blood NLR, SII, and MHR are positively associated with CRAO incidence, highlighting their potential as early predictive markers. The combined NLR and MHR index further enhances diagnostic accuracy and may facilitate timely assessment of CRAO severity by ophthalmologists and internists.
Keywords: Central retinal artery occlusion; Severity; Neutrophil-to-lymphocyte ratio; Monocyte-to-high-density lipoprotein cholesterol ratio; Systemic immune-inflammation index